The recovery from agro-industrial wastes provides different profiles of anti-inflammatory polyphenols for tailored applications - Abbasi-Parizad, Parisa; Scarafoni, Alessio; Pilu, Roberto; Scaglia, Barbara; De Nisi, Patrizia; Adani, Fabrizio (Frontiers in Sustainable Food Systems, 2022)
Food and agro-industrial processing produce great amount of side-stream and waste materials that are excellent source of bioactive molecules such as phenolic compounds which recovery of them can be beneficial to human for many industrial applications such as flavor compounds, and therapeutic applications like antimicrobial, anti-cancer, anti-inflammatory and etc. The treatments and extraction techniques have the major effect on the recovery of bioactive compounds. In this work the conventional and green extraction methods have been reviewed for five most produced crop in Italy; Grape Pomace (GP), Tomato Pomace (TP), Olive Pomace (OP), Citrus Pomace (CP) and Spent Coffee Grounds (SCG), presenting the extraction yield and the main class of phenolic classes, demonstrating anti-inflammatory in vitro and in vivo studies via describing their molecular mechanism of action.